SISTEM INFORMASI PEMASARAN ONLINE PADA ARCA PRODUCTION (Information Technology and Telematics, 2015)
Abstract- At this time the marketing area Arca prodution only in areas Weleri alone and marketing system is still done manually, just word of mouth customers who come to Arca Production or performed using a regular telephone, or by way of direct consumers come to Arca prodution to get information so that marketing is less effective and not widespread. Objectives to be achieved is to make online marketing information system on Arca Production capable of dealing with the problems that arise in the marketing activities on Arca Production. The results in this study is the online marketing information system on the new Production Arca can assist in managing marketing Arca Production in Production Arca more quickly and effectively with an efficient time Keywords – Information System, Marketing, Arca Production